Necessidades de familiares da pessoa internada em unidade de terapia intensiva: uma perspectiva compreensiva para a humanização do cuidar - Santos, Lia Cristina Galvão dos (1998)
My professional background as a nurse at an Intensive Care Unit (ICU) has given me the opportunity to establish professional relationship with ICU patients' family members. Those acquaintances allowed me to experience situations that led me to the accomplishment of this study. I sought to understand the assistance needs of ICU patients' family members in order to analyze the means through which nurses can contribute to attend those needs. So, taking Alfred Schutz's comprehensive sociology as a guide, to apprehend the typical action to search for counseling, I was able to detect the concrete needs of those family members. Thus, I grasped that the lived type family of the ICU patient expect to receive information about the hospitalized person, ready to share his/her care-taking with the ICU's professional team. ln that sense, I understand that the attendance to those needs must support care-taking reevaluation, where Health Professionals/Nurses should mediate their actions on the basis of an effective professional-family-patient social relationship, bearing in mind that the humanization of care (human-action) does necessarily goes through the sharing of perspectives in life-world.